Normative-legal regulation in the sphere of intellectual property and its relationship with the plans of scientific and technological development of the country - D. P. Fedulkin; V. G. Zinov (Ekonomika Nauki)
The article presents an overview of public policy measures in the field of identification, consolidation and inventory of rights to the results of intellectual activity with a high potential of industrial use. Proposals for the development of mechanisms of legal protection of individual intellectual property objects are substantiated. The instructive and methodical regulation of works on registration of results of scientific and technical activity under the state contracts is analyzed. Attention is paid to the complexity of the procedure of passing and agreeing the final results of their implementation. Methodological approaches to the improvement of identification and inventory of protectable results of intellectual activity obtained in the course of execution of state contracts as part of the organization’s activities in the field of innovation and technological development in order to implement the business strategy in the domestic and global markets are proposed.